Assesment of Damage in Juvenile Idiopathic Arthritis: Single Center Experience - Sevda Asadova; Ayşenur Paç Kısaarslan; Sümeyra Özdemir Çiçek; Nihal Şahin; Sema Nur Taşkın; Şeyda Doğantan; Muammer Hakan Poyrazoğlu (Galenos Publishing House, 2022)
Introduction:It is essential to evaluate the activation and the articular and extra-articular damage during the Juvenile Idiopathic Arthritis(JIA) disease course. Objectives:This study aimed to evaluate the damage status and affecting factors in JIA patients. Methods:Juvenile Arthritis Damage Index articular(JADI-A) and extra-articular(E) were evaluated in 204 JIA patients who had been followed up for two years andmore. JADI-A and E affecting factors were assessed by univariate and multivariate logistic regression analysis. Results: In this study,127(62.6%) of the patients were female. The median age was 13(IQR: 11-16), and the age at diagnosis was 7(IQR: 4-10) years. The median follow-up time was 5(IQR: 4-8) years. Ninety-two(45.3%) patients had comorbid diseases. JADI-A were median:0(min-max: 0-24), JADI-E were median:0(min-max:0-4).The annual attacks number [OR:1,759 (CI:1,300-2,379],p:<0,001),annual eritrocyte sedimantation rate (ESR) [OR:1,072(CI:1,021-1,125),p:0.005] were effective on JADI-A scores. The CRP at the first admission [OR:1.007(CI: 1,000-1,014), p:0.037], the annual ESR[OR:1,051(CI:1,008-1,095),p:0.019] were found to be effective on the JADI-E. The ideal cut-off point of the  attacks number and ESR affecting JADI-A scores were 1.38[AUC:0.734(0.641-0.828),p:0.001] and 14.32[AUC:0.617(0.514-0.721),p:0.027], respectively. The ideal cut-off point of the CRP and ESR affecting JADI-E scores were 13,25[AUC:0,662(0,541-0,782),p:0,009],and15,10[AUC:0.674(0.567-0.780),p:0.002], respectively. Steroid related complications such as, obesity in 12 (5.9%), hirsutism in 3 (1.5%), transient adrenal suppression in 14 (6.9%), 8 (3.9%), and osteoporosis were detectedin 7 (3.4%) patients. Conclusion: We have shown that parameters used routinely can be helpful to predict damage. We also think that new criteria should be added to the scoring.